DEVELOPMENT OF STUDENT WORKSHEETS (SWS) BASED ON REALISTIC MATHEMATICAL EDUCATION (RME) FOR MATERIAL SYSTEM OF LINEAR EQUATIONS OF TWO VARIABLES - Melma Rohani, (Mathematics Research and Education Journal, 2021)
This study aims to produce teaching materials in the form of valid and practical RME-based worksheets on two-variable linear equation system materials for students of SMP N 1 Bangkinang Kota and find out whether these worksheets have a potential effect on meaningful learning for students. The method used is the development method with the Plomp model with the preliminary analysis stage, development stage, and assessment stage. The subjects of this study were 8th grade students of SMP N 1 Bangkinang Kota. Data collection methods used are questionnaires, documentation, and interviews. The result of this research is to get an RME-based worksheet with a valid and practical two-variable linear equation system material. LKPD validity based on content, presentation, and language. The developed LKPD is in accordance with the characteristics of the RME with a percentage of 76.7%. Based on the presentation, the LKPD is well structured with a percentage of 80%. Meanwhile, based on language, LKPD has used good and correct language where there are no students who misunderstand and have multiple interpretations when reading it with a percentage of 95%. The practicality of the LKPD can be seen from the students being able to use the LKPD well.